Study of surface microstrains by electron speckle-interferometrymethods - Gokhman, Olexsandr; Kondrya, Marianna (Lviv Politechnic Publishing House, 2017)
Despite the fact that speckle interferometry methods began to develop more than 30 years ago, they still remain a rather exotic laboratory tool that has not received wide practical application in tensometry measurements and flaw detection. There are two reasons. The first one is the problem to interpret the interferograms by the right way. The second one is the extremely low measurement speed, which makes it impossible to use these methods for study of fast processes. In this paper we propose the advanced algorithm for electronic speckle interferometry (ESPI) method, which uses the arctangent of the intensity ratio of the speckles of two quarter-phase shifted specklograms, from that the position of the surface points with a known time step is calculated. Summing the increments of displacements after each measurement, we obtain a picture of the distribution of the strains of the surface of the object under study in the 3-dimensional representation customary for the experimenter. This approach effectively solves the first mentioned problem. While considering the second problem, it is shown that the measurement speed can be raised to the speed of the camera used (up to 1000 measurements per second in the flesh) if at the calibration stage a pair of speckles on the spectrograph is determined, whose phase is shifted by a quarter, and then take the arctangent of their ratio Intensities. In this case, there is no need to displace the reference beam, and the calculation of the displacement of the surface is made entirely from one specklogram only. Despite the fact that in this case the resolving power of the method bit decreases, the measurement speed increases substantially and there is no effect of the dynamic characteristics of the elements of the reference arm of the speckle interferometer on the measurement result, which is especially important in high-speed photography. The suggested algorithm for ESPI provides the extension of the diapason of recorded microstrains to hundreds of microns as well as on-line observation in 3D mode. New perspectives of nanoscale technologies could be opened on this way.
Keywords: speckle interferometry; tensometry measurements; space distribution of strains